Model‐informed drug development of autologous CAR‐T cell therapy: Strategies to optimize CAR‐T cell exposure leveraging cell kinetic/dynamic modeling - Anna M. Mc Laughlin; Peter A. Milligan; Cassian Yee; Martin Bergstrand (CPT: Pharmacometrics & Systems Pharmacology, 2023)
Abstract Autologous Chimeric antigen receptor (CAR‐T) cell therapy has been highly successful in the treatment of aggressive hematological malignancies and is also being evaluated for the treatment of solid tumors as well as other therapeutic areas. A challenge, however, is that up to 60% of patients do not sustain a long‐term response. Low CAR‐T cell exposure has been suggested as an underlying factor for a poor prognosis. CAR‐T cell therapy is a novel therapeutic modality with unique kinetic and dynamic properties. Importantly, “clear” dose‐exposure relationships do not seem to exist for any of the currently approved CAR‐T cell products. In other words, dose increases have not led to a commensurate increase in the measurable in vivo frequency of transferred CAR‐T cells. Therefore, alternative approaches beyond dose titration are needed to optimize CAR‐T cell exposure. In this paper, we provide examples of actionable variables – design elements in CAR‐T cell discovery, development, and clinical practice, which can be modified to optimize autologous CAR‐T cell exposure. Most of these actionable variables can be assessed throughout the various stages of discovery and development as part of a well‐informed research and development program. Model‐informed drug development approaches can enable such study and program design choices from discovery through to clinical practice and can be an important contributor to cell therapy effectiveness and efficiency.